Feed and Swaddle: An Alternative to Infant Sedation for Craniofacial Imaging. (November 2019) - Esmonde, Nick; Jedrzejewski, Breanna; Fitzpatrick, Beth; Koh, Jeffrey; Bardo, Dianna; Urbinelli, Leo; Crupi, Lisa; Oliverio, Maureen; Selden, Nathan R.; Kuang, Anna
Objective: The gold standard for diagnosis of craniosynostosis is a clinical examination and motionless head computed tomography (CT). Computed tomography sedation is associated with increased cost, resource utilization, medical, and possible developmental risks. This study investigates whether a "feed and swaddle" protocol can be used to achieve diagnostic quality craniofacial imaging without the use of infant sedation. Design: Prospective cohort study. Setting: Tertiary academic medical center. Patients: Ninety patients <18 months of age undergoing evaluation for craniosynostosis from 2012 to 2018. Interventions: A feed and swaddle protocol. Main Outcome Measures: Diagnostic level imaging without the use of infant sedation. Results: Eighty-five (94%) achieved a diagnostic quality craniofacial CT scan using the "feed and swaddle" method. Mean patient age was 24.0 ± 10.0 weeks. Craniosynostosis was diagnosed in 74% of patients. Mean age of patients with successful completion of a CT scan was 23.7 ± 9.6 weeks, compared to 27.2 ± 17.1 weeks for unsuccessful completion. Mean weight for the successful group was 15.6 ± 2.9 pounds and 15.9 ± 2.5 pounds for the unsuccessful group. Mean travel distance was 59.2 ± 66.5 miles for successful patients and 66.5 ± 61.5 miles for unsuccessful patients. For the unsuccessful patients, there were no delays in surgical planning or scheduling. Conclusion: The "feed and swaddle" protocol described here is an effective alternative to infant sedation for motionless craniofacial CT imaging.